Georgia Architectural and Historic Properties Survey of 405, 407, and 409 West St., Valdosta, Ga. - Smith, Bartholomew; Smith, Freda (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of 405, 407, and 409 West St., Valdosta, Ga. December 1980. 3 very similar clapboard sided houses with hipped tin roof. Shed porch held up by square posts. Double hung sash windows with 2/2 lights. Set on brick piers. Poor condition. Date of Construction: Circa 1920. 3 typical functional houses in a densely populated area settled by middle to low income. Has significance as part of a potential N.R. district.
Georgia Architectural and Historic Properties Survey of 405, 407, and 409 West St., Valdosta, Ga. December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 3 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 79.1 MB (83,046,931 bytes).
Keywords: Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Valdosta (Ga.)